Eksplorasi Etnomatematika Dan Geometri Pada “Rumoh Aceh” - Nur Azmi; Siti Nurhaliza; Darajatul Ula; Dwi Syifa; Suhaimi; Rossa Aprillia (Department of Master Program on Mathematics Education Faculty of Teacher Training and Education State Islamic Institute of Lhokseumawe, Indonesia, 2021)
Culture and religion are two very sacred things that cannot be separated in the life of the Acehnese people. Every activity in the life of the Acehnese is inseparable from religious values ​​that have even become culture, one of which is applied in the